ANALISIS PRODUKTIVITAS ALAT BERAT PADA PEKERJAAN PILE CAP PROYEK PEMBANGUNAN FLY OVER MRANGGEN-GODONG - Agatha Adhitya Buton; Agus Subiyanto; Muh. M. Ramadhan (Journal of Civil Engineering and Infrastructure Technology, 2026)
ABSTRACT As one of the modes of land transportation, road transportation in Indonesia dominates and is the most used transportation for transporting goods and services. Highways are an important component in the dynamics of development to grow and improve the development of national development in advancing general welfare as referred to in the Preamble to the 1945 Constitution of the Republic of Indonesia (Noor Mahmudah, 2019). In Indonesia, highway construction continues to be improved, both repair and maintenance efforts, as well as the construction of new roads. This study aims to determine the type of heavy equipment used and calculate the efficiency of heavy equipment productivity in the pile cap work of the Mranggen-Godong flyover construction project. The research method used is descriptive qualitative to explain the results of heavy equipment calculations based on calculation data collected through documentation techniques and literature reviews. Based on the research results, the productivity results of the heavy equipment used in the pile cap and abutment work for the Mranggen-Godong flyover construction project were obtained, namely excavators of 739.615 m3/hour, dump trucks 96.149 m3/hour, bar cutters 8,789.66 kg/hour, bar benders 6,665.65 kg/hour, and concrete mixer trucks 24.001 m3/hour. Keyword: Productivity, Heavy Equipment, Pile Cap, Abutment, Flyover, Consctruction Project